Studies on the Dynamics of Market Share’s Growth and Competition in Quadratic Mappings - C-René Dominique; Luis Eduardo Rivera Solis (Current Aspects in Business, Economics and Finance Vol. 5, 2022)
This chapter demonstrates that the observed output of any market, placed within the confine of a quadratic map, can characterize the state of that market. Such a strategy explains the increase of market shares and their potential dangers, the effects of broken scaling symmetry, and the boundaries of company competition for market shares.